ENERGETIC PARTICLES IN TOKAMAK PLASMAS - Sharapov, S. E. (Sergei E.) (BOCA RATON : CRC PRESS, 2021)
The study of energetic particles in magnetic fusion plasmas is key to the development of next-generation "burning" plasma fusion experiments, such as the International Thermonuclear Experimental Reactor (ITER) and the Demonstration Power Station (DEMO). This book provides a comprehensive introduction and analysis of the experimental data on how fast ions behave in fusion-grade plasmas, featuring the latest ground-breaking results from world-leading machines such as the Joint European Torus (JET) and the Mega Ampere Spherical Tokamak (MAST). It also details Alfvenic instabilities, driven by energetic ions, which can cause enhanced transport of energetic ions. MHD spectroscopy of plasma via observed Alfvenic waves called "Alfvn spectroscopy" is introduced and several applications are presented. This book will be of interest to graduate students, researchers, and academics studying fusion plasma physics. Features: Provides a comprehensive overview of the field in one cohesive text, with the main physics phenomena explained qualitatively first. Authored by an authority in the field, who draws on his extensive experience of working with energetic particles in tokamak plasmas. Is suitable for extrapolating energetic particle phenomena in fusion to other plasma types, such as solar and space plasmas.
OCLC-licensed vendor bibliographic record.
Keywords: Tokamaks; Plasma (Ionized gases); Solar energetic particles; Magnetohydrodynamics; SCIENCE / Energy; SCIENCE / Physics